Maternal enrichment increases infantile spatial amnesia mediated by postnatal neurogenesis modulation - López-Oropeza, Grecia; Durán, Pilar; Martínez-Canabal, Alonso (Frontiers in Behavioral Neuroscience, 2022)
Infantile amnesia, the inability to form long-lasting episodic memories, is a phenomenon extensively known but with no clear understanding of its origins. However, a recent study showed that high rates of hippocampal postnatal neurogenesis degrade episodic-like memories in infants a few days after memory acquisition. Additionally, new studies indicate that exposure to an enriched environment in mice leads to high hippocampal neurogenesis in their offspring. Nevertheless, it is still unclear how this intergenerational trait affects the persistence of hippocampal memories. Therefore, we evaluated spatial memory retention in the offspring of enriched female mice after weaning to address this question. Ten days after spatial learning, we tested memory retention, observing that the offspring of enriched dams increased spatial memory failure; this finding correlates with high proliferation rates in the hippocampus. Furthermore, we evaluated the causal relationship between postnatal hippocampal neurogenesis and memory failure using the antiproliferative drug temozolomide, which rescued spatial memory retrieval. Finally, we evaluated neuronal activity in the hippocampus quantifying the cells expressing the immediate early gene c-Fos. This evaluation showed engram modifications between groups. This neural activity pattern indicates that the high neurogenesis rates can modify memory engrams and cognitive performance. In conclusion, the inherited increase of hippocampal neurogenesis by enriched dams leads to plastic changes that exacerbate infantile amnesia in a spatial task.